2002
DOI: 10.1128/jcm.40.5.1862-1865.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii f. sp. hominis Is Not Infectious for SCID mice

Abstract: The infectious power of Pneumocystis carinii f. sp. hominis was explored by inoculating SCID mice intranasally with either P. carinii f. sp. hominis or P. carinii f. sp. muris isolates. Only mice inoculated with mouse parasites developed Pneumocystis pneumonia, as assessed by microscopy and PCR. These results suggest that humans do not contract pneumocystosis from animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Eight weeks postinfection, all animals harbored a high P. carinii burden and were euthanized. Their lungs were dissected to isolate organisms that were cryopreserved while remaining highly infectious [12,24,25]. …”
Section: Methodsmentioning
confidence: 99%
“…Eight weeks postinfection, all animals harbored a high P. carinii burden and were euthanized. Their lungs were dissected to isolate organisms that were cryopreserved while remaining highly infectious [12,24,25]. …”
Section: Methodsmentioning
confidence: 99%
“…This study demonstrated that Pneumocystis could not be transmitted between mice and ferrets [6]. This observation was soon followed by similar results that showed Pneumocystis from rabbits, rats, monkeys, and humans were not infectious for mice [reviewed in 7]. Thus, available data indicates that each mammalian species that contracts PcP has its own strain or species of Pneumocystis .…”
Section: Pneumocystis Is Not a Zoonosismentioning
confidence: 96%
“…Pneumocystis organisms recovered from different mammalian hosts are genetically distinct, and attempts at cross-species transmission have not been successful [13]. Furthermore, the requirements for Pneumocystis growth in vitro have not been determined, making the study of life cycle and biology a significant challenge.…”
Section: Introductionmentioning
confidence: 99%